DIVERSI SEBAGAI MEKANISME PENYELESAIAN PERKARA PIDANA ANAK: STUDI PERBANDINGAN INDONESIA DAN SINGAPURA - Rizqullah, Kharis Tegar; Apriyani, Rini; grizelda, Grizelda (Jurnal Ilmiah Advokasi, 2025)
This study aims to analyze and compare the implementation of diversion as a mechanism for resolving juvenile criminal cases within the juvenile justice systems of Indonesia and Singapore. The research employs a doctrinal method using a statutory approach combined with a comparative approach. The analysis focuses on differences in regulatory frameworks, implementation mechanisms, and the roles of law enforcement authorities in applying diversion in both countries. The findings reveal that although Indonesia and Singapore both recognize diversion as an alternative to formal criminal proceedings for children, significant differences exist in terms of normative regulation, procedural implementation, and institutional support. Singapore demonstrates a more integrated diversion model, supported by strong institutional infrastructure, while Indonesia continues to face challenges related to coordination, consistency in application, and the effective realization of child protection objectives. This study concludes that Singapore’s diversion practices offer valuable insights for strengthening and reforming diversion policies in Indonesia, particularly to enhance their effectiveness, align them with the best interests of the child, and reinforce the principles of restorative justice.Keywords: Diversion; Juvenile Justice System; Juvenile Criminal Cases; Comparative Study; Restorative Justice